The Innovative Teaching Strategies in Numeracy and Literacy to Achieve SDGs: A Systematic Literature Review - Caridah, Caridah; Pramono, Suwito Eko; Yulianto, Arief; Raharjo, Tri Joko (Universitas Negeri Semarang, 2024)
The pursuit of Sustainable Development Goals (SDGs) has driven significant advancements in global educational practices, particularly in the areas of numeracy and literacy. This study explores innovative teaching strategies designed to enhance these foundational skills, with a focus on their role in achieving SDG targets such as equitable access to quality education and promoting lifelong learning opportunities for all. The primary aim is to evaluate the effectiveness of these strategies in diverse educational contexts worldwide. A systematic literature review was conducted, analyzing data sourced from the Scopus database, covering publications from 2014 to 2024. The review included a detailed examination of 68 studies that met the inclusion criteria. The methodology involved the use of bibliometric tools like VOSviewer for mapping research themes and identifying trends in the field. The analysis revealed three major thematic clusters, highlighting the critical roles of numeracy, literacy, and their integration in educational strategies. The results indicate substantial improvements in student learning outcomes, critical thinking skills, and overall educational quality through the application of innovative teaching strategies in numeracy and literacy. These findings underscore the necessity of a holistic approach to education, integrating multiple competencies to effectively address the educational needs identified in SDG 4. The study concludes that the continued refinement and implementation of these strategies are crucial for advancing global educational objectives aligned with sustainable development. This research contributes valuable insights into the design and sustainability of educational policies and practices, offering a pathway to achieving broader educational and societal goals.